THE ROLE OF EFFICIENCY MEDIATION IN THE EFFECT OF BANKS SIZE ON BANK PROFITABILITY IN INDONESIA - Ruslan, Andi; Pahlevi, Cepi; Alam, Syamsu; Nohong, Mursalim (Hasanuddin Economics and Business Review, 2019)
The purpose of this study was to analyze the mediating role of bank efficiency in the effect of bank size on bank profitability. The research sample is 25 banks that have a minimum core capital of Rp. 5,000,000,000,000 and publish financial statements in full during 2010-2017. The data analysis technique in this study is path analysis (path analysis) with the help of AMOS software (Analysis of Moment Structure). The results of the study found that; 1) bank size has a positive and significant effect on bank efficiency; 2) bank size has a positive and not significant effect on bank profitability; 3) bank efficiency has a positive and significant effect on bank profitability. 4) bank efficiency is able to mediate the effect of bank size on bank profitability.